The bZIP Transcription Factor HAC-1 Is Involved in the Unfolded Protein Response and Is Necessary for Growth on Cellulose in Neurospora crassa - Montenegro-Montero, Alejandro; Goity, Alejandra; Larrondo, Luis F. (PLOS ONE, 2015)
High protein secretion capacity in filamentous fungi requires an extremely efficient system for protein synthesis, folding and transport. When the folding capacity of the endoplasmic reticulum (ER) is exceeded, a pathway known as the unfolded protein response (UPR) is triggered, allowing cells to mitigate and cope with this stress. In yeast, this pathway relies on the transcription factor Hac1, which mediates the up-regulation of several genes required under these stressful conditions. In this work, we identified and characterized the ortholog of the yeast HAC1 gene in the filamentous fungus Neurospora crassa. We show that its mRNA undergoes an ER stress-dependent splicing reaction, which in N. crassa removes a 23 nt intron and leads to a change in the open reading frame. By disrupting the N. crassa hac-1 gene, we determined it to be crucial for activating UPR and for proper growth in the presence of ER stress-inducing chemical agents. Neurospora is naturally found growing on dead plant material, composed primarily by lignocellulose, and is a model organism for the study of plant cell wall deconstruction. Notably, we found that growth on cellulose, a substrate that requires secretion of numerous enzymes, imposes major demands on ER function and is dramatically impaired in the absence of hac-1, thus broadening the range of physiological functions of the UPR in filamentous fungi. Growth on hemicellulose however, another carbon source that necessitates the secretion of various enzymes for its deconstruction, is not impaired in the mutant nor is the amount of proteins secreted on this substrate, suggesting that secretion, as a whole, is unaltered in the absence of hac-1. The characterization of this signaling pathway in N. crassa will help in the study of plant cell wall deconstruction by fungi and its manipulation may result in important industrial biotechnological applications.